Negotiating Self-Loss Through Denial Defence Mechanism: A Freudian Reading of Rosé’s Album Rosie (2024) - Evi Irawanti Br Saragih (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
This study examines the negotiation of self-loss through the denial defence mechanism in Rosé’s album Rosie (2024) using a Freudian psychoanalytic approach. Popular music is positioned as a cultural text that articulates psychological conflict and emotional vulnerability, particularly within toxic romantic relationships. Employing qualitative textual analysis and close reading, this research focuses on three selected songs namely Number One Girl, Toxic Till the End, and Stay a Little Longer to explore how denial operates as an ego defence in managing emotional pain and relational trauma. The findings reveal that denial functions through three interrelated forms: affective denial, cognitive denial, and symbolic denial. Rather than serving merely as a temporary protective mechanism, denial operates continuously to sustain emotional attachment, delay confrontation with loss, and gradually erode the subject’s autonomy and identity. This process results in a negotiated form of self-loss, in which the subject remains psychologically functional while experiencing progressive fragmentation of the self. By reading the album as a coherent psychological narrative rather than isolated songs, this study contributes a novel conceptual framework for understanding the dynamics of self-loss and denial in popular music, while extending psychoanalytic approaches to the analysis of contemporary female musical texts and affective trauma.